Digital resistance in the Middle East : new media activism in everyday life - Wheeler, Deborah L., 1965- (Edinburgh University Press, 2017)
This book argues that Internet diffusion and use in the Middle East enables meaningful micro-changes in citizens' lives, even in states where no Arab Spring revolution occurred.